Administering ArcGIS for Server - Nasser, Hussein (Professional expertise distilled, 2014)
This book is a practical, step-by-step tutorial providing a complete reference guide to the setup, installation, and administration of ArcGIS Server technology. If you are a GIS user, analyst, DBA, or programmer with a basic knowledge of ESRI GIS, then this book is for you.